How does Market Access affect Smallholder Behavior? The Case of Tobacco Marketing in Malawi - Wouter Zant (Tinbergen Institute, 2012)
Transaction costs play a key role in the behaviour of smallholders in developing countries. We exploit the quasi experimental design of the introduction of an additional tobacco auction floor in Malawi in order to investigate the impact of a reduction in transaction costs and improved market access on yield and underlying smallholder's decisions on production and area of tobacco, the major cash crop in Malawi. Estimations are based on annual data by Extension Planning Area, 198 in total, fully covering Malawi, for 2003-04 to 2009-10. The estimation results support a statistically significant positive impact of the introduction of a new auction floor on tobacco yield and production of smallholders. Yield increases over the years to 21-25% above base year level. Smallholder production increases are of a similar size with a larger variation, ranging from 12% to 30%. The evidence further suggests that smallholder area is not affected. Results are shown to be robust after controlling for rainfall, fertilizer use, tobacco prices, maize prices and after including the lagged dependent variable.
urn:NBN:nl:ui:31-1871/38505
Keywords: D23; O13; O55; Q11; Q13; 330; transaction costs; market access; subsistence; food & cash crops; Malawi; Africa; Tabakanbau; Markteintritt; Kleinbauern; Malawi